Approximate Analytical Solution of the Influences of Magnetic Field and Chemical Reaction on Unsteady Convective Heat and Mass Transfer of Air, Water, and Electrolyte Fluids Subject to Newtonian Heating in a Porous Medium - Sulemana, M.; Seini, Y. I.; Makinde, O. D. (Advances in Mathematical Physics, 2024)
This paper addresses the unsteady hydrodynamic convective heat and mass transfer of three fluids namely air, water, and electrolyte solution past an impulsively started vertical surface with Newtonian heating in a porous medium under the influences of magnetic field and chemical reaction. Suitable dimensionless parameters are used to transform the flow equations and the approximate analytic method employed to solve the flow problem. The results are illustrated graphically for the velocity, temperature, and concentration profiles. Though, low Prandtl numbers produce high-thermal boundary layer thickness, however, as a novelty, the presence of the magnetic field delayed the convection motion hence, the thermal boundary layer thickness is greater for water with high Pr = 7.0 as compared to air with low Pr = 0.71 and electrolyte solution with low Pr = 1.0. Practically, water with a high-Prandtl number can effectively absorb and release heat. This makes water useful in applications such as geothermal heat pumps and solar thermal collectors, industrial processes such as chemical reactions, distillation, and drying, and in oceanography in predicting the movement and behavior of ocean currents, which in turn can impact weather patterns and climate. Another major observation from the study is that the rate of cooling associated with air, water, or electrolyte impacts differently on the product being cooled.